Estetika Panggung Postmodern Teater Visual Robert Wilson dengan Pendekatan Kritik Seni - Farik Eko Sulistiyo (Dance and Theatre Review, 2024)
The uniqueness of Wilson's visual theatre greatly influenced the artistic world of the stage. Where architectural elements are not only a place setting but perceive the form of space and time so that the audience feels spoiled. The method used is the art criticism approach, art criticism is not only about judging, but how we must know and describe the artist's life and environment, what factors and elements shape techniques and styles so that they can influence his work. By describing, analyzing, and assessing the artist's work, then the next stage is to judge and evaluate. The purpose of this article is to record art history so that visuals are not just a stage phenomenon, but a science. The lack of articles about Wilson's theatre has led to further research and discussion from other perspectives. Especially visual theatre articles in Indonesia. It is hoped that this article will be a trigger for theatre researchers in Indonesia to reveal how to criticize art properly and correctly and that Indonesian theatre researchers can rediscover the true nature of Wilson's visual theatre.Keywords: stage aesthetics, postmodern, visual theatre, robert wilson, art criticism